Avanços na Terapia Gênica para Doenças Neurológicas: Promessas e Desafios - Ottilo Cavassani Neto, Rosiclerk (2024)
This review article discusses recent advances in gene therapy for neurological diseases, highlighting both the promises and challenges of this innovative approach. The introduction contextualizes the importance of the topic, emphasizing the transformative potential of gene therapy in treating severe and often intractable neurological conditions, such as neurodegenerative diseases, rare neurological disorders, and psychiatric disorders. The methodology involved a comprehensive search of major scientific databases, using specific terms to identify relevant studies that address various aspects of gene therapy in the neurological context. The results were synthesized into four main topics: gene therapy for neurodegenerative diseases, for rare neurological disorders, for psychiatric and other neurological disorders, and the challenges and limitations of this therapeutic approach. Each topic highlighted the most significant findings and the most promising strategies, such as the use of lentiviral and adeno-associated vectors, as well as the application of gene editing techniques like CRISPR/Cas9. The discussion explored the implications of these findings, with an emphasis on the need to overcome technical barriers, such as the effective delivery of genes to the central nervous system, and the ethical and economic considerations associated with the clinical implementation of these therapies. The conclusion reinforces the potential of gene therapy to revolutionize the treatment of neurological diseases, while also acknowledging the challenges that still need to be addressed. This study contributes to the field by providing a comprehensive overview of current advances and limitations, offering a solid foundation for future research.